Effectiveness of high flow‐volume intermittent hemodiafiltration during and after intervention to prevent contrast‐induced nephropathy in patients with advanced chronic kidney disease: A pilot study. Issue 6 (5th December 2019) - Oyamada, Naofumi; Hamanaka, Ichiro; Fujioka, Ayumu; Iwasaku, Toshihiro; Minami, Takeya; Fujie, Hiroaki; Ueda, Kinzo
Abstract: Objectives: We analyzed the effect of high flow‐volume intermittent hemodiafiltration (HF‐IHDF) on patients with advanced chronic kidney disease (CKD) undergoing procedures requiring administration of contrast medium. Background: There is no effective method for preventing contrast‐induced nephropathy (CIN), especially in patients with advanced CKD. We established HF‐IHDF as a renal protective therapy with a filtration flow rate up to 5 times greater than standard continuous HDF. In this study, we tested whether HF‐IHDF could prevent CIN in patients with advanced CKD more effectively than saline hydration only. Methods: We retrospectively analyzed the incidence of CIN and clinical outcomes up to 1 year after performance of a procedure in 76 patients with advanced CKD. HF‐IHDF was performed from just before the procedure until 2.5 hr after it. Hydration with 0.9% saline was also administered. Results: The incidence of CIN was significantly lower in the HF‐IHDF group than the saline group 2–3 days (0%, 0/76 patients vs. 9.3%, 5/54 patients; p  < .05) and 1 month (3.9%, 3/76 patients vs. 14.8%, 8/54 patients; p  < .05) after intervention. No difference between the two groups was detected in the proportion of patients requiring permanent hemodialysis within 1 year after intervention or the 1 year mortality rate. However, the number of patients free from progression of renal dysfunction after 1 year of follow‐up was significantly higher in the HF‐IHDF group (86.8%, 66/76 patients vs. 64.8%, 35/54 patients; p  < .01). Conclusions: HF‐IHDF during and after interventional procedure requiring administration of contrast medium may prevent CIN in patients with advanced CKD.